Quality of Dried Gourami (Osphronemus gouramy) under Different Drying Methods - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2016)
Fish is an important source of high-quality protein essential for human consumption. Fish is a highly perishable foodstuff with a very short shelf life. Drying is a complex thermal process in which unsteady heat and moisture transfer occur simultaneously. The drying process effects on protein quality and composition of fish. Gourami (Osphronemus gouramy) has high nutrient content. However it has a short shelf life. It’s necessary to remove its moisture content via drying. In our current study, the effect of different drying methods such as sun drying, microwave drying and oven drying to the quality of dried gourami (Osphronemus gouramy) was investigated. Results clearly revealed that microwave drying was the best selection to get a perfect dried fish quality for a long term storage.Keywords: Osphronemus gouramy, Sun drying, Microwave drying, Oven drying, Water activity, Histamin, Aerobic plate count, Shelf life.